Increase in gross primary production of boreal forests balanced out by increase in ecosystem respiration - Pulliainen, Jouni; Aurela, Mika; Aalto, Tuula; Böttcher, Kristin; Cohen, Juval; Derksen, Chris; Heimann, Martin; Helbig, Manuel; Kolari, Pasi; Kontu, Anna; Krasnova, Alisa; Launiainen, Samuli; et al. (Elsevier, 2024)
Changes in the net carbon sink of boreal forests constitute a major source of uncertainty in the future global carbon budget and, hence, climate change projections. The annual net ecosystem exchange of carbon dioxide (CO2) controlling the terrestrial carbon stock results from the small difference between respiratory CO2 release and the photosynthetic CO2 uptake by vegetation. The boreal forest, and the boreal biome in general, is regarded as a persistent and even increasing net carbon sink. However, decreases in photosynthetic CO2 uptake and/or concurrent increases in respiratory CO2 release under a changing climate may turn boreal forests from a net sink to a net source of CO2. Here, we assessed the interannual variability of the boreal forest net CO2 sink-source strength and its two component fluxes from 1981 to 2018. Our remote sensing approach - trained by net CO2 flux observations at eddy covariance sites across the circumpolar boreal forests - employs satellite-derived retrievals of snowmelt timing, landscape freeze-thaw status, and yearly maximum estimates of the normalized difference vegetation index as a proxy for peak vegetation productivity. Our results suggest that for the period 2000–2018, the mean annual evergreen boreal forest CO2 photosynthetic uptake (gross primary productivity) was 2.8±0.2 Pg C y−1 (1.6±0.1 Pg C y−1 for Eurasia and 1.2±0.1 Pg C y−1 for North America). In contrast to earlier studies results obtained here do not indicate a clear increasing trend in the circumpolar evergreen boreal forest CO2 sink. The increase in photosynthetic CO2 uptake is compensated by increasing respiratory releases with both component fluxes showing considerable interannual variabilities.
Keywords: remote sensing of boreal forests; remote sensing of cryosphere; carbon balance; net carbon sink; eddy covariance; passive microwave remote sensing